Determinan Of Skin Disease In Scavengers - Melva Saragih; David Siagian (Akupun Tour Publisher, 2022)
Background: Skin disease is a skin disorder with symptoms of itching and is characterized objectively by patches, rashes, or inflammation. Skin diseases are often experienced by scavengers. Purpose: The purpose of this study wasto determine the factors associated with the incidence of skin disease in scavengers in garbage dumps. Method: This study is an observational analytic study with a cross-sectional study design from January to August 2021. The population is scavengers who scavenge around the garbage dumpsat Medan Polonia.Data analysis methodsusing Chi-square with a significance level of 0.05. Result: The results of this study are that there is a relationship between personal hygiene (0.05) and a history of skin disease (0.03) with the incidence of skin disease in scavengers around the garbage dumpsat Medan Polonia, and there isno relationship between personal protective equipment and skin disease incidence in scavengers in around the garbage dumpsat Medan Polonia. Conclusion: It is hoped that related agencies such as Public health center at Medan Polonia, are expected to be able to empower scavengers and educate scavengers to be better able to maintain and maintain personal health in order to avoid health problems in this case, especially diseases caused by the work environment.